Physical exercise, cognitive performance, affective responses and mental health: challenges and perspectives. - Deslandes, Andrea Camaz; dos Santos, Tony Meireles (Revista de Educação Física / Journal of Physical Education, 2017)
Introduction: The prophylactic and therapeutic effects of physical exercise in cardiovascular and metabolic diseases are recognized. In the last ten years, studies have shown the association of active lifestyle with prevention and treatment of mental illnesses as well as the improvement of executive functions throughout life. Nevertheless, methodological problems make it difficult to use the evidence on practical clinic. Objective: To analyze recent evidence on the effects of physical exercise for cognitive performance improvement, prevention and treatment of mental illness and affective responses generated by exercise, highlighting the gaps that should be fulfilled and challenges on this knowledge area. Conclusion: Physical exercise contributes to reduce risks for mental illness and to enhance clinical response in patients with mood and anxiety disorders, and neurodegenerative diseases. Cognitive function, mainly executive functions, has been observed in different age groups. Affective responses generated during the exercise are influenced by various extrinsic and intrinsic factors and can contribute to the development of new prescription strategies to increase physical exercise adherence. Studies with greater methodological rigor and variable exercise prescriptions, like frequency, duration, intensity and the type of the exercise should be conduced for better targeting practical application of the knowledge. Exercício físico, desempenho cognitivo e saúde mental: perspectivas e desafios Introdução: O efeito profilático e terapêutico do exercício físico em doenças cardiovasculares e metabólicas é reconhecido. Nos últimos dez anos, estudos mostraram associação entre o estilo de vida ativo e a prevenção e o tratamento de doenças mentais, assim como, a melhora das funções executivas em diferentes faixas etárias. Entretanto, questões metodológicas dificultam a utilização das evidências na prática clínica. Objetivo: Apresentar as evidências recentes sobre o efeito do exercício físico na melhora do desempenho cognitivo, prevenção e tratamento de doenças mentais e respostas afetivas geradas pelo exercício, destacando lacunas a serem investigadas e desafios nessa área de conhecimento. Conclusão: O exercício físico contribui para a redução do risco de desenvolvimento de doenças mentais e melhora da resposta clínica de pacientes com transtornos de humor e de ansiedade e doenças neurodegenerativas. A melhora da função cognitiva, em especial as funções executivas, é observada em diferentes faixas etárias. As respostas afetivas geradas durante o exercício são influenciadas por diversos fatores extrínsecos e intrínsecos e podem contribuir para o desenvolvimento de novas estratégias de prescrição para a melhora da aderência ao exercício físico. Estudos com maior rigor metodológico e maior controle de variáveis de prescrição de exercícios, como frequência, duração, intensidade e tipo de exercício devem ser feitos para o melhor direcionamento da aplicação prática do conhecimento.